PENGEMBANGAN MAJALAH IPA BERBASIS LITERASI SAINS PADA MATERI SISTEM EKSKRESI KELAS VIII SMP NEGERI 1 BOTOMUZOI - Lase, Imelda Sofiana; Harefa, Agnes Renostini; Waruwu, Toroziduhu; Zega, Novelina Andriani (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
ABSTRACT Teaching materials play an important role in the learning process as they serve as guidelines for teachers in delivering instructional content and as learning resources for students. However, the teaching materials used in schools are still dominated by conventional forms that are less engaging and have not fully supported the optimal development of students’ scientific literacy. This condition indicates the need for innovative teaching materials that are more contextual, interactive, and capable of increasing students’ engagement in science learning.This study aims to develop and evaluate the feasibility, practicality, and effectiveness of science literacy–based science magazine teaching materials on the topic of the excretory system for eighth-grade students at SMP Negeri 1 Botomuzoi. The study employed a Research and Development (R&D) method using the ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects included material experts, language experts, design experts, and eighth-grade students. Data were collected through expert validation questionnaires, student response questionnaires, and learning outcome tests.The results showed feasibility levels of 85.46%, 84.4%, and 86.6% from the respective experts, all categorized as very feasible. The practicality level reached 96.95% (very practical), while the effectiveness test indicated a 90.32% learning mastery level (very effective). Therefore, the science literacy–based science magazine is appropriate to be used as an innovative teaching material to improve students’ scientific literacy. ABSTRAK Bahan ajar memegang peranan penting dalam proses pembelajaran karena berfungsi sebagai pedoman bagi guru dalam menyampaikan materi sekaligus sebagai sumber belajar bagi peserta didik. Namun, bahan ajar yang digunakan di sekolah masih didominasi oleh bentuk konvensional yang kurang menarik dan belum sepenuhnya mampu mendukung pengembangan literasi sains peserta didik secara optimal. Kondisi ini menunjukkan perlunya inovasi bahan ajar yang lebih kontekstual, interaktif, dan mampu meningkatkan keterlibatan peserta didik dalam pembelajaran sains. Penelitian ini bertujuan untuk mengembangkan serta mengevaluasi kelayakan, kepraktisan, dan efektivitas bahan ajar berupa Majalah IPA berbasis literasi sains pada materi sistem ekskresi bagi peserta didik kelas VIII di SMP Negeri 1 Botomuzoi. Penelitian menggunakan metode Research and Development (R&D) dengan model ADDIE yang meliputi tahap Analysis, Design, Development, Implementation, dan Evaluation. Subjek penelitian meliputi validator ahli materi, ahli bahasa, ahli desain, serta peserta didik kelas VIII. Data dikumpulkan melalui angket validasi ahli, angket respons peserta didik, dan tes hasil belajar. Hasil penelitian menunjukkan tingkat kelayakan sebesar 85,46%, 84,4%, dan 86,6% dari masing-masing ahli dengan kategori sangat layak. Tingkat kepraktisan mencapai 96,95% (sangat praktis), sedangkan efektivitas menunjukkan ketuntasan belajar 90,32% (sangat efektif). Dengan demikian, Majalah IPA berbasis literasi sains layak digunakan sebagai bahan ajar inovatif untuk meningkatkan literasi sains peserta didik.